2018
DOI: 10.1037/tra0000319
|View full text |Cite
|
Sign up to set email alerts
|

Association of posttraumatic nightmares and psychopathology in a military sample.

Abstract: The replicativeness of nightmares appears to be a key variable for understanding the relationship between posttraumatic nightmares and PTSD, whereas nightmare frequency and distress appear to be more aptly defined as generic markers of mental health. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
4
18
0
1
Order By: Relevance
“…Interestingly, after accounting for NPS scores, general distress, trauma symptoms, and neuroticism no longer significantly predicted nightmare frequency. This is noteworthy considering that nightmare frequency has been consistently related to neuroticism (Schredl, 2003) and current general distress (Lee & Suh, 2016) and that nightmares have been identified as a core feature of posttraumatic stress reactions (de Dassel, Wittmann, Protic, Höllmer, & Gorzka, 2018). Therefore, the current findings suggest the possibility of a nightmare-specific personality dimension that might contribute to previous consistently observed relationships between nightmares and manifestations of distress (Klѳůzová Kráčmarová & Plháková, 2015; Lee & Suh, 2016; Schredl, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, after accounting for NPS scores, general distress, trauma symptoms, and neuroticism no longer significantly predicted nightmare frequency. This is noteworthy considering that nightmare frequency has been consistently related to neuroticism (Schredl, 2003) and current general distress (Lee & Suh, 2016) and that nightmares have been identified as a core feature of posttraumatic stress reactions (de Dassel, Wittmann, Protic, Höllmer, & Gorzka, 2018). Therefore, the current findings suggest the possibility of a nightmare-specific personality dimension that might contribute to previous consistently observed relationships between nightmares and manifestations of distress (Klѳůzová Kráčmarová & Plháková, 2015; Lee & Suh, 2016; Schredl, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Another noradrenergic receptor antagonist that has been used primarily to combat disordered sleep in individuals with PTSD is the α1-AR antagonist prazosin. Prazosin has shown promise in ameliorating nightmares and sleep disturbances associated with PTSD (Raskind et al, 2003 ; Taylor et al, 2008 ; Koola et al, 2014 ; Writer et al, 2014 ; de Dassel et al, 2017 ; Keeshin et al, 2017 ; Miller et al, 2017 ; Short et al, 2018 ). However, a recent clinical trial demonstrated that prazosin did not ameliorate sleep-related disturbances in military veterans with PTSD (Raskind et al, 2018 ).…”
Section: Ne and Ptsdmentioning
confidence: 99%
“…Although sleep loss is inherent to operational missions, chronic sleep loss is also prevalent among non-deployed SMs. Military personnel report sleep disturbances (e.g., insufficient or non-restorative sleep, insomnia, nightmares) before, during, and after deployment at alarming rates (Breen, Blankley, & Fine, 2017;Caldwell, Knapik, & Lieberman, 2017;de Dassel, Wittmann, Protic, Hollmer, & Gorzka, 2017;Troxel et al, 2015). Numbers have continuously grown over the years and have well surpassed prevalence and incidence rates of the general population.…”
Section: Sleep Disturbances In Military Populationsmentioning
confidence: 99%